Biopolymer‐Based Biomatrices – Organic Strategies to Combat Micronutrient Deficit for Dynamic Agronomy. Issue 16 (22nd April 2022) - Malik, Ritu; Saxena, Reena; Warkar, Sudhir G.
Abstract: Agronomy inexorably contributes an eminent role in food nutriment and the economic upswing of a country. Micronutrients though required exiguously; are vital for the growth, health, and higher yields of the crops. Micronutrient supplementation at a controlled rate in an economical and eco‐friendly way is the major challenge, an agro‐researcher has to deal with. The potential of scientific research entails the usage of natural, renewable, and abundant raw materials that endow a solution to the agronomical challenges of today's world. Besides being non‐hazardous, biopolymer‐based matrices are pertinent materials that act as a reservoir of micronutrients and are a boon for agronomy, this review explores the synthesis of biomatrices, loading of micronutrients into the bio‐matrix, kinetics, and mechanism of release of micronutrients along with the citations of the biopolymer‐based matrices used till date for the controlled release of micronutrients that would be rewarding for forthcoming research. These green polymeric matrices have been explored a lot for the release of micronutrients iron, copper, and zinc but more research is required for the supplementation of boron, molybdenum, and manganese. The bio‐matrices applied as micronutrient carrier vehicle in agronomy results in enhanced growth, high crop yield, and sustainability. Abstract : The biopolymer‐based matrices can be applied for sustainable agronomical practices viz. micronutrient supplementation. Different methods of synthesis of bio‐matrices along with different methods of loading micronutrients into bio‐matrices are surveyed. Further, different biopolymers employed in synthesis of bio‐matrices and micronutrients supplied through their usage, are reviewed till date, along with the kinetics and release mechanism of micronutrients. Based on survey, it is observed that green polymeric matrices have been explored a lot for the release of micronutrients: iron, copper, and zinc but more exploration is required for boron, molybdenum, and manganese. This review will aid in further research on fabrication of biomatrices to be applied as a micronutrient carrier vehicle for sustainable agronomy.